Silicon carbide and high entropy alloy reinforced aluminum-based composite material and preparation method thereof
Through acoustic resonance technology and sintering process, bionic core-shell structure SiC and high-entropy alloy reinforced aluminum-based composite materials were prepared, which solved the problems of high brittleness and uneven phase dispersion of aluminum-based composite materials, and achieved high strength, high wear resistance and good plasticity.
Patent Information
- Application Number
- CN202411631034.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-15
AI Technical Summary
In practical applications, existing aluminum-based composite materials have problems such as high brittleness and uneven reinforcing phase dispersion, resulting in interfacial stress concentration and material failure.
Through acoustic resonance technology and sintering process, a bionic core-shell structure SiC and high-entropy alloy reinforced aluminum-based composite material with modulus gradient are designed and prepared to achieve uniform dispersion of the enhanced phase and interfacial stress relief.
It significantly improves the strength, wear resistance and plasticity of aluminum-based composite materials, reduces density, and is suitable for high-performance automotive brake discs and other applications.
Smart Images

Figure CN119144865B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of high-strength and wear-resistant aluminum-based composite materials, and in particular to a silicon carbide and high-entropy alloy reinforced aluminum-based composite material and a preparation method thereof. Background Art
[0002] As a key component of the vehicle braking system, the performance of brake discs is directly related to driving safety and industry development. Traditional brake disc materials, such as cast iron and steel, often show limitations such as poor thermal conductivity, insufficient wear resistance, and easy thermal decay under extreme working conditions, such as high-speed braking, frequent braking, or heavy load conditions. These shortcomings restrict the safe development of high-performance vehicles and new energy vehicles. In addition, cast iron or steel materials have high density, and heavier finished components are not conducive to energy conservation and emission reduction as well as the green development of the automotive industry.
[0003] Aluminum-based composite materials are expected to become the next generation of brake disc materials due to their unique physical and mechanical properties, especially excellent wear resistance, high thermal conductivity and lightweight properties.
[0004] However, the aluminum-based composite materials of the prior art have the following problems:
[0005] 1) In practical applications, it often faces the problem of high brittleness, which is mainly due to the huge difference in modulus between the reinforcement phase (such as silicon carbide SiC particles) and the aluminum matrix, resulting in stress concentration at the interface when subjected to force, thus causing crack propagation and material failure;
[0006] 2) On the other hand, the uneven dispersion of the reinforcement phase using traditional processes can easily induce stress concentration in the early stages of deformation, seriously damaging the plasticity of the aluminum-based composite material.
[0007] In response to the above-mentioned problems in the prior art, the present invention provides a method for preparing silicon carbide and high entropy alloy reinforced aluminum-based composite materials, which innovatively proposes a design and preparation method of a bionic core-shell structure SiC and high entropy alloy reinforced aluminum-based material with a modulus gradient: a multi-layer cross-scale bionic core-shell structure of an aluminum alloy matrix, a high entropy alloy, and SiC with a modulus gradient is realized through acoustic resonance technology and sintering process.
[0008] In the technical solution of the present invention, a cross-scale modulus gradient is formed through structural design, which effectively alleviates the modulus mismatch problem between the traditional ceramic reinforcement phase and the matrix, and significantly reduces the interface stress concentration; on the other hand, the acoustic resonance technology adopted by the present invention is based on the principle of acoustic flow, and uses mechanical resonance to generate large-amplitude vibrations, thereby generating acoustic flow inside, so that the material as a whole is fully fluidized, generating a mixed motion, and significantly improving the dispersion effect of the reinforcement phase; the aluminum-based composite material prepared by the present invention has both high strength and high wear resistance as well as good plasticity, and is expected to promote the safe application of aluminum-based composite materials in automotive brake discs. Summary of the invention
[0009] The purpose of the present invention is to provide a silicon carbide and high entropy alloy reinforced aluminum-based composite material and a preparation method thereof. The method realizes a multi-layer cross-scale bionic core-shell structure of an aluminum alloy matrix, a high entropy alloy, and SiC with a modulus gradient through acoustic resonance technology and a sintering process. Not only is the preparation process simple and low in cost, but the prepared cross-scale bionic core-shell structure SiC and high entropy alloy reinforced wear-resistant aluminum-based composite material has excellent comprehensive mechanical properties (high strength, high wear resistance, good plasticity) and low density.
[0010] To achieve the above object, the present invention is implemented by the following technical solutions:
[0011] A method for preparing a silicon carbide and high entropy alloy reinforced aluminum-based composite material, comprising the following preparation steps:
[0012] S1: spheroidization treatment of micron 2024Al alloy powder;
[0013] S2: Preparation of submicron high entropy alloy powder;
[0014] S3: high entropy alloy @2024Al powder preparation;
[0015] S4: Preparation of nano-spherical SiC particles;
[0016] S5: SiC coated high entropy alloy @2024Al powder preparation;
[0017] S6: degassing of the package;
[0018] S7: Hot isostatic pressing.
[0019] As a further improvement of this scheme,
[0020] The specific operation steps of S1: spheroidization of micron 2024Al alloy powder are as follows:
[0021] S11 Put 2024Al alloy powder with an average powder size of 10-30 μm into a ball mill for low-energy ball milling at a speed of 150-250 rpm, a ball-to-material mass ratio of 5:1-10:1, a ball milling time of 8h-24h, and a ball diameter of 1.5-3mm;
[0022] S12 The powder is then sieved by a vibration sieving + airflow classification method to obtain micron-sized spherical 2024Al with a particle size not greater than 20 μm.
[0023] As a further improvement of this scheme,
[0024] The specific steps of S2: preparation of submicron high entropy alloy powder are as follows:
[0025] Al, Fe, Co, Cr, and Ni powders with an average powder size of 1~20μm are placed in a ball mill for high-energy ball milling mechanical alloying, wherein the Al content is 5%~30%; the Fe content is 5~30%, the Co content is 5~30%; the Cr content is 5%~30%, and the Ni content is 5%~30%, and the five elements total 100%. The ball mill speed is 350~500 rpm, the ball-to-material mass ratio is 10:1~20:1, the ball milling time is 20h~100h, the ball diameter is 3mm, 5mm, and 9mm, and the dosage is 1:3:6 respectively. The powder is then sieved by vibration sieving + airflow classification method to obtain submicron ultrafine high entropy alloy powder with a particle size between 500nm ~5μm;
[0026] Wherein, the ball milling medium is made of zirconium oxide.
[0027] As a further improvement of this scheme,
[0028] The specific operation steps of S3: high entropy alloy @2024Al powder preparation are:
[0029] The 2024Al spherical powder prepared by S1 and the mechanically alloyed high entropy alloy powder prepared by S2 were coated with a core-shell structure using acoustic resonance technology.
[0030] The mass ratio of 2024Al spherical powder is 70%~90%, and the mass ratio of high entropy alloy powder is 30%~10%;
[0031] The resonance frequency is 55~70Hz, and the acceleration generated by the resonance is set to 60g~80g, where 1g=9.8m / s 2 The mixing and coating time is 40-60 min, until the high entropy alloy powder completely coats the 2024Al powder to form a micron-scale core-shell structure;
[0032] During the entire acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation.
[0033] As a further improvement of this scheme,
[0034] The specific operation steps of S4: preparation of nano-spherical SiC particles are as follows:
[0035] Nano-spherical SiC reinforcement phase is prepared by low-temperature liquid nitrogen ball milling technology:
[0036] S41 puts the initial irregular SiC particles with an average particle size of 1 μm into a ball mill for controlled low-temperature ball milling, with a rotation speed of 400-500 rpm, a ball-to-material ratio of 10:1-20:1, a ball milling time of 50h-100h, a ball diameter of 3mm, and the ball milling medium is made of zirconium oxide;
[0037] S42 The powder is then screened by a vibration screening + airflow classification method to obtain nano-scale nearly spherical SiC particles with a particle size of no more than 500 nm.
[0038] As a further improvement of this scheme,
[0039] The specific steps of preparing the S5: SiC-coated high entropy alloy @2024Al powder are as follows:
[0040] The high entropy alloy @2024Al spherical powder prepared in the third step and the nano-spherical SiC particles prepared in the fourth step were coated with a core-shell structure using the acoustic resonance technology again;
[0041] The mass ratio of high entropy alloy @2024Al spherical powder is 80%~90%, and the mass ratio of SiC particles is 20%~10%. The resonance frequency is 60~70Hz, and the acceleration generated by the resonance is set to 70g~80g, where 1g=9.8m / s 2 , the mixing and coating time is 40-60 min, until the nano-SiC completely coats the high entropy alloy @2024Al powder to form a cross-scale core-shell structure;
[0042] During the entire acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation.
[0043] As a further improvement of this scheme,
[0044] The specific operation steps of S6: bag degassing are:
[0045] The mixed powders are placed in an aluminum bag and degassed at 420-500°C. When the vacuum degree in the bag is better than 3×10 -3 After Pa, the package is sealed by welding.
[0046] As a further improvement of this scheme,
[0047] The specific operation steps of S7: hot isostatic pressing sintering are:
[0048] S71 Place the above-mentioned package in a hot isostatic pressing furnace and heat it to 480~550℃ at a heating rate of 10~40℃ / min. At the same time, apply pressure evenly around the package. The final sintering pressure is 200MPa. Ensure that the heating and pressurization are carried out simultaneously and reach;
[0049] S72 Then, the heat and pressure are maintained for 120 minutes under this condition, and the heating is stopped and the load is removed. After the furnace is cooled to room temperature, the vacuum is broken and the package is taken out to obtain a cylindrical blank.
[0050] A silicon carbide and high entropy alloy reinforced aluminum-based composite material is prepared by a preparation method of a silicon carbide and high entropy alloy reinforced aluminum-based composite material. The silicon carbide and high entropy alloy reinforced aluminum-based composite material is a cross-scale bionic core-shell structure SiC and high entropy alloy reinforced aluminum-based composite material.
[0051] In the present invention, the submicron high entropy alloy and the nano-SiC particle reinforcement phase are uniformly coated on the 2024Al alloy matrix in sequence through the acoustic resonance technology, forming a cross-scale bionic core-shell structure with a modulus gradient, which effectively alleviates the weak interface problem between the ceramic reinforcement phase and the matrix of the traditional aluminum-based composite material, and significantly improves the uneven dispersion problem of the reinforcement phase, avoids stress concentration, and obtains an aluminum-based composite material with high strength, high wear resistance and good plasticity, which is expected to become the next generation of automotive brake disc material.
[0052] The method for preparing high-purity bulk single crystal titanium metal of the present invention has the following beneficial effects:
[0053] 1) Low cost and lightweight: The raw materials used in the present invention are 2024Al alloy, metal element powders such as Al and Fe, and SiC powder, which are low in cost and low in density, and can achieve lightweight brake discs.
[0054] 2) Uniform dispersion of the reinforcing phase: The acoustic resonance technology used in the present invention is based on the principle of acoustic flow. It uses mechanical resonance to generate large-amplitude vibrations and generate acoustic flow inside, so that the material as a whole is fully fluidized and a mixing motion is generated, which significantly improves the dispersion effect of the reinforcing phase.
[0055] 3) Cross-scale modulus gradient design to alleviate interface stress concentration: The aluminum-based composite material prepared by the present invention is a cross-scale core-shell structure aluminum-based composite material composed of nano-scale SiC, submicron-scale high entropy alloy and micron-scale 2024Al, and its comprehensive mechanical properties such as wear resistance and tensile strength are excellent and controllable. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 This is a schematic structural diagram of the "bionic core-shell structure" silicon carbide high entropy alloy cross-scale reinforced aluminum-based composite material of the present invention. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical solutions and advantages of the present invention more clear, the following embodiments and the accompanying drawings are combined to illustrate the present invention. Figure 1 The present invention will be further described:
[0058] Example 1
[0059] A method for preparing a "core-shell structure" silicon carbide high entropy alloy cross-scale reinforced aluminum-based composite material in this embodiment includes the following steps:
[0060] Step 1: Spheroidization of micronized 2024Al alloy powder
[0061] The 2024Al alloy powder with an average powder size of 10μm was placed in a ball mill for low-energy ball milling at a speed of 250 rpm, a ball-to-material mass ratio of 10:1, a ball milling time of 24h, and a ball diameter of 1.5mm. The powder was then sieved by vibration sieving + airflow classification to obtain micron-sized spherical 2024Al with a particle size of no more than 20μm;
[0062] Preferably, the ball milling medium is made of stainless steel.
[0063] Step 2: Preparation of submicron high entropy alloy powder
[0064] Al, Fe, Co, Cr, and Ni powders with an average powder size of 10μm were placed in a ball mill for high-energy ball milling mechanical alloying, wherein the Al content was 30%; the Fe content was 20%, the Co content was 20%; the Cr content was 20%, and the Ni content was 10%, and the five elements totaled 100%. The ball mill speed was 500 rpm, the ball-to-material mass ratio was 20:1, the ball milling time was 100h, the ball diameters were 3mm, 5mm, and 9mm, and the dosages were 1:3:6, respectively. The powder was then sieved by vibration sieving + airflow classification method to obtain submicron ultrafine high entropy alloy powder with a particle size between 500nm and 5μm;
[0065] Preferably, the ball milling medium is made of zirconium oxide.
[0066] Step 3: Preparation of high entropy alloy coated 2024Al powder
[0067] Acoustic resonance technology was used to coat the 2024Al spherical powder prepared in the first step and the mechanically alloyed high entropy alloy powder prepared in the second step with a core-shell structure. The mass ratio of 2024Al spherical powder was 70%, and the mass ratio of high entropy alloy powder was 30%. The resonance frequency was 55~70Hz, the acceleration generated by the resonance was set to 60g~80g (1g=9.8m / s2), and the mixing coating time was 40~60min, until the high entropy alloy powder completely coated the 2024Al powder to form a micron-scale core-shell structure. Argon gas was input for gas protection during the entire acoustic resonance treatment process to prevent oxidation.
[0068] Step 4: Preparation of Nano-spherical SiC Particles
[0069] Nano-spherical SiC reinforcement phase was prepared by low-temperature liquid nitrogen ball milling technology. The initial irregular SiC particles with an average particle size of 1 μm were placed in a ball mill for controllable ball milling. The speed was 500 rpm, the ball-to-material ratio was 20:1, the ball milling time was 100 h, the ball diameter was 3 mm, and the ball milling medium was all made of zirconium oxide. The powder was then screened by vibration screening + airflow classification to obtain nano-scale nearly spherical SiC particles with a particle size of no more than 500 nm.
[0070] Step 5: Preparation of SiC and high entropy alloy coated 2024Al powder
[0071] The high entropy alloy @2024Al spherical powder prepared in the third step and the nano-spherical SiC particles prepared in the fourth step were coated with the core-shell structure using the acoustic resonance technology again. The mass ratio of the high entropy alloy @2024Al spherical powder is 80%, and the mass ratio of the SiC particles is 20%. The resonance frequency is 70Hz, and the acceleration generated by the resonance is set to 80g (1g=9.8m / s 2 ), the mixing and coating time is 60min, until the nano-SiC completely coats the high entropy alloy @2024Al powder to form a cross-scale core-shell structure. During the entire acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation.
[0072] Step 6: Degassing of the package
[0073] The mixed powders were placed in an aluminum bag and degassed at 450°C. When the vacuum degree in the bag was better than 3×10 -3 After Pa, the package is sealed by welding.
[0074] Step 7: Hot Isostatic Pressing
[0075] The above-mentioned sleeve is placed in a hot isostatic pressing furnace and heated to 550°C at a heating rate of 10°C / min. At the same time, pressure is evenly applied all around the sleeve. The final sintering pressure is 200MPa, ensuring that the heating and pressurization are carried out and reached simultaneously; then, the heat and pressure are maintained and sintered under this condition for 120 minutes, the heating is stopped, the load is unloaded, and the vacuum is broken after the furnace cools to room temperature, the sleeve is taken out, and a cylindrical billet is obtained.
[0076] The multi-scale particle-reinforced aluminum-based composite material prepared by the above method in this embodiment has a tensile strength of 745 MPa, an elongation at break of 3.5%, a wear loss of less than 0.008 g, and good plasticity and wear resistance.
[0077] Example 2
[0078] A method for preparing a "bionic core-shell structure" silicon carbide high entropy alloy cross-scale reinforced aluminum-based composite material in this embodiment comprises the following steps:
[0079] Step 1: Spheroidization of micronized 2024Al alloy powder
[0080] The 2024Al alloy powder with an average powder size of 10μm was placed in a ball mill for low-energy ball milling at a speed of 250 rpm, a ball-to-material mass ratio of 10:1, a ball milling time of 24h, and a ball diameter of 1.5mm. The powder was then sieved by vibration sieving + airflow classification to obtain micron-sized spherical 2024Al with a particle size of no more than 20μm;
[0081] Preferably, the ball milling medium is made of stainless steel.
[0082] Step 2: Preparation of submicron high entropy alloy powder
[0083] Al, Fe, Co, Cr, and Ni powders with an average powder size of 10μm were placed in a ball mill for high-energy ball milling mechanical alloying, wherein the Al content was 30%; the Fe content was 20%, the Co content was 20%; the Cr content was 20%, and the Ni content was 10%, and the five elements totaled 100%. The ball mill speed was 500 rpm, the ball-to-material mass ratio was 20:1, the ball milling time was 100h, the ball diameters were 3mm, 5mm, and 9mm, and the dosages were 1:3:6, respectively. The powder was then sieved by vibration sieving + airflow classification method to obtain submicron ultrafine high entropy alloy powder with a particle size between 500nm and 5μm;
[0084] Preferably, the ball milling medium is made of zirconium oxide.
[0085] Step 3: Preparation of high entropy alloy coated 2024Al powder
[0086] The 2024Al spherical powder prepared in the first step and the mechanically alloyed high entropy alloy powder prepared in the second step were coated with a core-shell structure using acoustic resonance technology. The mass ratio of 2024Al spherical powder is 90%, and the mass ratio of high entropy alloy powder is 10%. The resonance frequency is 70Hz, the acceleration generated by the resonance is set to 80g (1g=9.8m / s2), and the mixing coating time is 60min, until the high entropy alloy powder completely coats the 2024Al powder to form a micron-level core-shell structure. Argon gas is input during the entire acoustic resonance process for gas protection to prevent oxidation.
[0087] Step 4: Preparation of Nano-spherical SiC Particles
[0088] Nano-spherical SiC reinforcement phase was prepared by low-temperature liquid nitrogen ball milling technology. The initial irregular SiC particles with an average particle size of 1 μm were placed in a ball mill for controllable ball milling. The speed was 500 rpm, the ball-to-material ratio was 20:1, the ball milling time was 100 h, the ball diameter was 3 mm, and the ball milling medium was all made of zirconium oxide. The powder was then screened by vibration screening + airflow classification to obtain nano-scale nearly spherical SiC particles with a particle size of no more than 500 nm.
[0089] Step 5: Preparation of SiC and high entropy alloy coated 2024Al powder
[0090] The high entropy alloy @2024Al spherical powder prepared in the third step and the nano-spherical SiC particles prepared in the fourth step were coated with the core-shell structure using the acoustic resonance technology again. The mass ratio of the high entropy alloy @2024Al spherical powder was 90%, and the mass ratio of the SiC particles was 10%. The resonance frequency was 70Hz, and the acceleration generated by the resonance was set to 80g (1g=9.8m / s 2 ), the mixing and coating time is 60min, until the nano-SiC completely coats the high entropy alloy @2024Al powder to form a cross-scale core-shell structure. During the entire acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation.
[0091] Step 6: Degassing of the package
[0092] The mixed powders were placed in an aluminum bag and degassed at 450°C. When the vacuum degree in the bag was better than 3×10 -3 After Pa, the package is sealed by welding.
[0093] Step 7: Hot Isostatic Pressing
[0094] The above-mentioned sleeve is placed in a hot isostatic pressing furnace and heated to 550°C at a heating rate of 10°C / min. At the same time, pressure is evenly applied all around the sleeve. The final sintering pressure is 200MPa, ensuring that the heating and pressurization are carried out and reached simultaneously; then, the heat and pressure are maintained and sintered under this condition for 120 minutes, the heating is stopped, the load is unloaded, and the vacuum is broken after the furnace cools to room temperature, the sleeve is taken out, and a cylindrical billet is obtained.
[0095] The multi-scale particle-reinforced aluminum-based composite material prepared by the above method in this embodiment has a tensile strength of 678 MPa, an elongation at break of 6.8%, a wear loss of less than 0.01 g, and good plasticity and wear resistance.
[0096] Example 3
[0097] A method for preparing a "bionic core-shell structure" silicon carbide high entropy alloy cross-scale reinforced aluminum-based composite material in this embodiment comprises the following steps:
[0098] Step 1: Spheroidization of micronized 2024Al alloy powder
[0099] The 2024Al alloy powder with an average powder size of 10μm was placed in a ball mill for low-energy ball milling at a speed of 250 rpm, a ball-to-material mass ratio of 10:1, a ball milling time of 24h, and a ball diameter of 1.5mm. The powder was then sieved by vibration sieving + airflow classification to obtain micron-sized spherical 2024Al with a particle size of no more than 20μm;
[0100] Preferably, the ball milling medium is made of stainless steel.
[0101] Step 2: Preparation of submicron high entropy alloy powder
[0102] Al, Fe, Co, Cr, and Ni powders with an average powder size of 10μm were placed in a ball mill for high-energy ball milling mechanical alloying, wherein the Al content was 10%; the Fe content was 25%, the Co content was 25%; the Cr content was 25%, and the Ni content was 15%, and the five elements totaled 100%. The ball mill speed was 500 rpm, the ball-to-material mass ratio was 20:1, the ball milling time was 100h, the ball diameters were 3mm, 5mm, and 9mm, and the dosages were 1:3:6, respectively. The powder was then sieved by vibration sieving + airflow classification method to obtain submicron ultrafine high entropy alloy powder with a particle size between 500nm and 5μm;
[0103] Preferably, the ball milling medium is made of zirconium oxide.
[0104] Step 3: High Entropy Alloy @2024Al Powder Preparation
[0105] The 2024Al spherical powder prepared in the first step and the mechanically alloyed high entropy alloy powder prepared in the second step were coated with a core-shell structure using acoustic resonance technology. The mass ratio of the 2024Al spherical powder was 90%, and the mass ratio of the high entropy alloy powder was 10%. The resonance frequency was 70 Hz, and the acceleration generated by the resonance was set to 80 g (1 g = 9.8 m / s 2 ), the mixing and coating time is 60min, until the high entropy alloy powder completely coats the 2024Al powder to form a micron-scale core-shell structure. During the entire acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation.
[0106] Step 4: Preparation of Nano-spherical SiC Particles
[0107] Nano-spherical SiC reinforcement phase was prepared by low-temperature liquid nitrogen ball milling technology. The initial irregular SiC particles with an average particle size of 1 μm were placed in a ball mill for controllable ball milling. The speed was 500 rpm, the ball-to-material ratio was 20:1, the ball milling time was 100 h, the ball diameter was 3 mm, and the ball milling medium was all made of zirconium oxide. The powder was then screened by vibration screening + airflow classification to obtain nano-scale nearly spherical SiC particles with a particle size of no more than 500 nm.
[0108] Step 5: Preparation of SiC-coated high entropy alloy @2024Al powder
[0109] The high entropy alloy @2024Al spherical powder prepared in the third step and the nano-spherical SiC particles prepared in the fourth step were coated with the core-shell structure using the acoustic resonance technology again. The mass ratio of the high entropy alloy @2024Al spherical powder was 90%, and the mass ratio of the SiC particles was 10%. The resonance frequency was 70Hz, and the acceleration generated by the resonance was set to 80g (1g=9.8m / s 2 ), the mixing and coating time is 60min, until the nano-SiC completely coats the high entropy alloy @2024Al powder to form a cross-scale core-shell structure. During the entire acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation.
[0110] Step 6: Degassing of the package
[0111] The mixed powders were placed in an aluminum bag and degassed at 450°C. When the vacuum degree in the bag was better than 3×10 -3 After Pa, the package is sealed by welding.
[0112] Step 7: Hot Isostatic Pressing
[0113] The above-mentioned sleeve is placed in a hot isostatic pressing furnace and heated to 550°C at a heating rate of 10°C / min. At the same time, pressure is evenly applied all around the sleeve. The final sintering pressure is 200MPa, ensuring that the heating and pressurization are carried out and reached simultaneously; then, the heat and pressure are maintained and sintered under this condition for 120 minutes, the heating is stopped, the load is unloaded, and the vacuum is broken after the furnace cools to room temperature, the sleeve is taken out, and a cylindrical billet is obtained.
[0114] The multi-scale particle-reinforced aluminum-based composite material prepared by the above method in this embodiment has a tensile strength of 612 MPa, an elongation at break of 9.7%, a wear loss of less than 0.013 g, and good plasticity and wear resistance.
[0115] Comparative Example 1
[0116] A method for preparing a "bionic core-shell structure" silicon carbide reinforced aluminum-based composite material in this comparative example comprises the following steps:
[0117] Step 1: Spheroidization of micronized 2024Al alloy powder
[0118] The 2024Al alloy powder with an average powder size of 10μm was placed in a ball mill for low-energy ball milling at a speed of 250 rpm, a ball-to-material mass ratio of 10:1, a ball milling time of 24h, and a ball diameter of 1.5mm. The powder was then sieved by vibration sieving + airflow classification to obtain micron-sized spherical 2024Al with a particle size of no more than 20μm;
[0119] Preferably, the ball milling medium is made of stainless steel.
[0120] Step 2: Preparation of Nano-spherical SiC Particles
[0121] Nano-spherical SiC reinforcement phase was prepared by low-temperature liquid nitrogen ball milling technology. The initial irregular SiC particles with an average particle size of 1 μm were placed in a ball mill for controllable ball milling. The speed was 500 rpm, the ball-to-material ratio was 20:1, the ball milling time was 100 h, the ball diameter was 3 mm, and the ball milling medium was all made of zirconium oxide. The powder was then screened by vibration screening + airflow classification to obtain nano-scale nearly spherical SiC particles with a particle size of no more than 500 nm.
[0122] Step 3: Preparation of SiC-coated 2024Al powder
[0123] The 2024Al spherical powder prepared in the third step and the nano-spherical SiC particles prepared in the fourth step were coated with a core-shell structure using acoustic resonance technology. The mass ratio of the 2024Al spherical powder was 80%, and the mass ratio of the SiC particles was 20%. The resonance frequency was 70 Hz, and the acceleration generated by the resonance was set to 80 g (1 g = 9.8 m / s 2 ), the mixing and coating time is 60min, until the nano-SiC completely coats the high entropy alloy @2024Al powder to form a cross-scale core-shell structure. During the entire acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation.
[0124] Step 6: Degassing of the package
[0125] The mixed powders were placed in an aluminum bag and degassed at 450°C. When the vacuum degree in the bag was better than 3×10 -3 After Pa, the package is sealed by welding.
[0126] Step 7: Hot Isostatic Pressing
[0127] The above-mentioned sleeve is placed in a hot isostatic pressing furnace and heated to 550°C at a heating rate of 10°C / min. At the same time, pressure is evenly applied all around the sleeve. The final sintering pressure is 200MPa, ensuring that the heating and pressurization are carried out and reached simultaneously; then, the heat and pressure are maintained and sintered under this condition for 120 minutes, the heating is stopped, the load is unloaded, and the vacuum is broken after the furnace cools to room temperature, the sleeve is taken out, and a cylindrical billet is obtained.
[0128] The tensile strength of the SiC reinforced aluminum-based composite material prepared by the above method in this comparative example is 561MPa, the elongation at break is only 1.5%, and the wear loss is less than 0.021g. It can be seen that compared with the conventional SiC particle reinforced aluminum-based composite material, the introduction of the high entropy alloy over-reinforcement phase can form a cross-scale bionic core-shell structure aluminum-based composite material with a modulus gradient, making the comprehensive mechanical properties of the aluminum-based composite material more excellent.
[0129] Comparative Example 2
[0130] A method for preparing a "bionic core-shell structure" silicon carbide high entropy alloy cross-scale reinforced aluminum-based composite material in this comparative example comprises the following steps:
[0131] Step 1: Spheroidization of micronized 2024Al alloy powder
[0132] The 2024Al alloy powder with an average powder size of 10μm was placed in a ball mill for low-energy ball milling at a speed of 250 rpm, a ball-to-material mass ratio of 10:1, a ball milling time of 24h, and a ball diameter of 1.5mm. The powder was then sieved by vibration sieving + airflow classification to obtain micron-sized spherical 2024Al with a particle size of no more than 20μm;
[0133] Preferably, the ball milling medium is made of stainless steel.
[0134] Step 2: Preparation of submicron high entropy alloy powder
[0135] Al, Fe, Co, Cr, and Ni powders with an average powder size of 10μm were placed in a ball mill for high-energy ball milling mechanical alloying, wherein the Al content was 30%; the Fe content was 20%, the Co content was 20%; the Cr content was 20%, and the Ni content was 10%, and the five elements totaled 100%. The ball mill speed was 500 rpm, the ball-to-material mass ratio was 20:1, the ball milling time was 100h, the ball diameters were 3mm, 5mm, and 9mm, and the dosages were 1:3:6, respectively. The powder was then sieved by vibration sieving + airflow classification method to obtain submicron ultrafine high entropy alloy powder with a particle size between 500nm and 5μm;
[0136] Preferably, the ball milling medium is made of zirconium oxide.
[0137] Step 3: Preparation of high entropy alloy coated 2024Al powder
[0138] The 2024Al spherical powder prepared in the first step and the mechanically alloyed high entropy alloy powder prepared in the second step were mixed and coated using conventional powder mixing technology. The mass ratio of 2024Al spherical powder was 90%, and the mass ratio of high entropy alloy powder was 10%. A V-type mixer was used with a speed of 20r / min and a time of 360min.
[0139] Step 4: Preparation of Nano-spherical SiC Particles
[0140] Nano-spherical SiC reinforcement phase was prepared by low-temperature liquid nitrogen ball milling technology. The initial irregular SiC particles with an average particle size of 1 μm were placed in a ball mill for controllable ball milling. The speed was 500 rpm, the ball-to-material ratio was 20:1, the ball milling time was 100 h, the ball diameter was 3 mm, and the ball milling medium was all made of zirconium oxide. The powder was then screened by vibration screening + airflow classification to obtain nano-scale nearly spherical SiC particles with a particle size of no more than 500 nm.
[0141] Step 5: Preparation of SiC and high entropy alloy coated 2024Al powder
[0142] The high entropy alloy @2024Al spherical powder prepared in the third step and the nano-spherical SiC particles prepared in the fourth step were mixed again using conventional powder mixing technology. The mass ratio of the high entropy alloy @2024Al spherical powder was 90%, and the mass ratio of the SiC particles was 10%. A V-type mixer was used with a speed of 20r / min and a mixing time of 360min to obtain an aluminum-based composite material powder.
[0143] Step 6: Degassing of the package
[0144] The mixed powders were placed in an aluminum bag and degassed at 450°C. When the vacuum degree in the bag was better than 3×10 -3 After Pa, the package is sealed by welding.
[0145] Step 7: Hot Isostatic Pressing
[0146] The above-mentioned sleeve is placed in a hot isostatic pressing furnace and heated to 550°C at a heating rate of 10°C / min. At the same time, pressure is evenly applied all around the sleeve. The final sintering pressure is 200MPa, ensuring that the heating and pressurization are carried out and reached simultaneously; then, the heat and pressure are maintained and sintered under this condition for 120 minutes, the heating is stopped, the load is unloaded, and the vacuum is broken after the furnace cools to room temperature, the sleeve is taken out, and a cylindrical billet is obtained.
[0147] The multi-scale particle reinforced aluminum-based composite material prepared by the above method in this embodiment has a tensile strength of 608 MPa, an elongation at break of 2.3%, and a wear loss of less than 0.017 g.
[0148] It can be seen that compared with the conventional V-type powder mixing technology, the acoustic resonance technology is conducive to enhancing the uniform dispersion of the phase and forming a cross-scale bionic core-shell structure aluminum-based composite material with a modulus gradient, which makes the comprehensive mechanical properties of the aluminum-based composite material more excellent.
[0149] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent changes made using the present invention are within the patent protection scope of the present invention.
Claims
1. A method for preparing a silicon carbide and high entropy alloy reinforced aluminum-based composite material, characterized in that: The method comprises the following preparation steps: S1: spheroidization treatment of micron 2024Al alloy powder; S2: Preparation of submicron high entropy alloy powder; S3: high entropy alloy @2024Al powder preparation; S4: Preparation of nano-spherical SiC particles; S5: SiC coated high entropy alloy @2024Al powder preparation; S6: degassing of the package; S7: hot isostatic pressing; The specific steps of S2: preparation of submicron high entropy alloy powder are as follows: Al, Fe, Co, Cr, and Ni powders with an average powder size of 1-20 mm are placed in a ball mill for high-energy ball milling mechanical alloying, wherein the Al content is 5%-30%; the Fe content is 5-30%, the Co content is 5-30%; the Cr content is 5%-30%, and the Ni content is 5%-30%, and the five elements total 100%; the ball milling speed is 350-500 rpm, the ball-to-material mass ratio is 10:1-20:1, the ball milling time is 20h-100h, the ball diameters are 3mm, 5mm, and 9mm, and the dosages are 1:3:6 respectively; then the powder is sieved by vibration sieving + airflow classification method to obtain submicron ultrafine high entropy alloy powder with a particle size between 500nm and 5μm; Wherein, the ball milling medium is made of zirconium oxide; The specific operation steps of S3: high entropy alloy @2024Al powder preparation are: The 2024Al spherical powder prepared by S1 and the mechanically alloyed high entropy alloy powder prepared by S2 were coated with a core-shell structure using acoustic resonance technology. The mass ratio of 2024Al spherical powder is 70%~90%, and the mass ratio of high entropy alloy powder is 30%~10%; The resonance frequency is 55~70Hz, and the acceleration generated by the resonance is set to 60g~80g, where 1g=9.8m / s 2 The mixing and coating time is 40-60 min, until the high entropy alloy powder completely coats the 2024Al powder to form a micron-scale core-shell structure; During the whole acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation; The specific steps of preparing the S5: SiC coated high entropy alloy @2024Al powder are as follows: The high entropy alloy @2024Al spherical powder prepared in the third step and the nano-spherical SiC particles prepared in the fourth step were coated with a core-shell structure using the acoustic resonance technology again; The mass ratio of high entropy alloy @2024Al spherical powder is 80%~90%, the mass ratio of SiC particles is 20%~10%, the resonance frequency is 60~70Hz, and the acceleration generated by resonance is set to 70g~80g, where 1g=9.8m / s 2 , the mixing and coating time is 40-60 min, until the nano-SiC completely coats the high entropy alloy @2024Al powder to form a cross-scale core-shell structure; During the whole acoustic resonance treatment process, argon gas is input for gas protection to prevent oxidation; The specific operation steps of S7: hot isostatic pressing sintering are: S71 Place the above-mentioned package in a hot isostatic pressing furnace and heat it to 480~550℃ at a heating rate of 10~40℃ / min. At the same time, apply pressure evenly around the package. The final sintering pressure is 200MPa. Ensure that the heating and pressurization are carried out simultaneously and reach; S72 Then, the heat and pressure are maintained for 120 minutes under this condition, and the heating is stopped and the load is removed. After the furnace is cooled to room temperature, the vacuum is broken and the package is taken out to obtain a cylindrical blank.
2. The method for preparing the silicon carbide and high entropy alloy reinforced aluminum-based composite material according to claim 1, characterized in that: The specific operation steps of S1: spheroidization of micron 2024Al alloy powder are as follows: S11 Put 2024Al alloy powder with an average powder size of 10-30 mm into a ball mill for low-energy ball milling at a speed of 150-250 rpm, a ball-to-material mass ratio of 5:1-10:1, a ball milling time of 8h-24h, and a ball diameter of 1.5-3mm; S12 The powder is then sieved by a vibration sieving + airflow classification method to obtain micron-sized spherical 2024Al with a particle size not greater than 20 μm.
3. The method for preparing the silicon carbide and high entropy alloy reinforced aluminum-based composite material according to claim 1, characterized in that: The specific operation steps of S4: preparation of nano-spherical SiC particles are as follows: Nano-spherical SiC reinforcement phase is prepared by low-temperature liquid nitrogen ball milling technology: S41 puts the initial irregular SiC particles with an average particle size of 1 mm into a ball mill for controllable low-energy ball milling, with a rotation speed of 400-500 rpm, a ball-to-material ratio of 10:1-20:1, a ball milling time of 50h-100h, a ball diameter of 3mm, and the ball milling medium is made of zirconium oxide; S42 The powder is then screened by a vibration screening + airflow classification method to obtain nano-scale nearly spherical SiC particles with a particle size of no more than 500 nm.
4. The method for preparing the silicon carbide and high entropy alloy reinforced aluminum-based composite material according to claim 1, characterized in that: The specific operation steps of S6: bag degassing are: The mixed powders are placed in an aluminum bag and degassed at 420-500°C. When the vacuum degree in the bag is better than 3×10 -3 After Pa, the package is sealed by welding.
5. The method for preparing the silicon carbide and high entropy alloy reinforced aluminum-based composite material according to claim 2, characterized in that: The ball milling medium is made of stainless steel.
6. A silicon carbide and high entropy alloy reinforced aluminum-based composite material, characterized in that: The silicon carbide and high entropy alloy reinforced aluminum-based composite material is prepared by the preparation method of any one of claims 1 to 5. The silicon carbide and high entropy alloy reinforced aluminum-based composite material is a cross-scale bionic core-shell structure SiC and high entropy alloy reinforced aluminum-based composite material.
Citation Information
Patent Citations
High-entropy alloy particle reinforced transition gradient interface metal matrix composite material and preparation method thereof
CN115921873A
Preparation method of multi-scale particle reinforced wear-resistant aluminum-based composite material
CN117165802A